Importancia de la variación de los niveles de amilasa en pacientes ingresados en el Hospital Isidro Ayora en la Unidad de Cuidados Intensivos con diagnóstico de intoxicación por inhibidores de colinesterasa en el periodo Diciembre 2010 a Octubre 2011 - Ruiz Zabaleta, Gabriela (2013)
Keywords; poisoning cholinesterase inhibitors, amylase. This research work was conducted in the Intensive Care Unit of the Provincial Hospital Isidro Ayora Cave, during the period December 2010 - October 2011, and was raised as specific objectives, "Knowing the frequency of patients with a diagnosis of poisoning by cholinesterase inhibitors in the intensive care unit, determine serum amylase levels as a marker of evolution and determine the relationship between levels of serum amylase and cholinesterase ". The research is descriptive. The sample was constituted by 25 patients who met the inclusion criteria at the time of admission to the emergency area, we used the data collection sheet which has the signs and symptoms of poisoning by cholinesterase inhibitors, and amylase values and serial cholinesterase in the Intensive Care Unit. From this investigation it is concluded that cholinesterase inhibitors poisoning prevalent in females with 64%, and ages between 19-40 years in 32%. Amylase levels were elevated in patients with organophosphate poisoning with an average 159.7UI, and Carbamate intoxicated with an average of 68.4 IU. The hospital stay in patients poisoned with organophosphorus is greater, with an average of 11 days. There is a positive association between organophosphate poisoning and elevated amylase at admission The ratio of amylase and cholinesterase in patients during hospitalization is highly related inversely.